2012
DOI: 10.3109/17453674.2012.702388
|View full text |Cite
|
Sign up to set email alerts
|

Systemic intermittent parathyroid hormone treatment improves osseointegration of press-fit inserted implants in cancellous bone

Abstract: Background and purpose Intermittent administration of parathyroid hormone (PTH) has an anabolic effect on bone, as confirmed in human osteoporosis studies, distraction osteogenesis, and fracture healing. PTH in rat models leads to improved fixation of implants in low-density bone or screw insertion transcortically.Material and methods We examined the effect of human PTH (1–34) on the cancellous osseointegration of unloaded implants inserted press-fit in intact bone of higher animal species. 20 dogs were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
1
19
0
1
Order By: Relevance
“…The finding that iPTH enhanced bone formation within our titanium implant is consistent with the beneficial effects of iPTH therapy on osseointegration seen in other models [17][18][19][20][21][22][23]35 . In our study, an increase in trabecular number, as opposed to trabecular thickness, appeared to be the primary structural change resulting from iPTH in the peri-implant region compared with the distal region.…”
Section: Peri-implantation Ipth Increased Osteoblast and Osteoclastsupporting
confidence: 76%
See 1 more Smart Citation
“…The finding that iPTH enhanced bone formation within our titanium implant is consistent with the beneficial effects of iPTH therapy on osseointegration seen in other models [17][18][19][20][21][22][23]35 . In our study, an increase in trabecular number, as opposed to trabecular thickness, appeared to be the primary structural change resulting from iPTH in the peri-implant region compared with the distal region.…”
Section: Peri-implantation Ipth Increased Osteoblast and Osteoclastsupporting
confidence: 76%
“…Previous studies of in vivo models suggested that iPTH improves osseointegration [17][18][19][20][21][22][23][29][30][31][32][33][34] . Previous studies on osseointegration, however, had substantial limitations, including (1) use of large animals (rabbits, sheep, and dogs) with accompanying high cost, lower throughput 17,19,30,31,[35][36][37][38] , and greater humanitarian concerns compared with those related to small-animal models; (2) nonphysiologic implant placement such as in the medullary canal or extra-articular locations 18,[20][21][22]32,39 ; and (3) reliance on cortical bone support for stability 18,[20][21][22]40 . In the present study, we used a newly developed murine model with an intra-articular titanium implant that was loaded through the knee joint and supported by the cancellous bone bed of the proximal part of the tibia.…”
Section: Peri-implantation Ipth Increased Osteoblast and Osteoclastmentioning
confidence: 99%
“…However, in a dog study of implant integration, small but significant effects were seen with 5µg/kg [21]. We chose this dose because when we are close to the lowest efficacious dose, the effects of possible contributing factors, such as loading, are more likely to make a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental details for these studies are found in the original publications [16][17][18][23][24][25][26][27][28]. In brief, retrieved bone-implant specimens are cut into two pieces.…”
Section: Modeling Approaches To Study Bone-implant Interfacementioning
confidence: 99%
“…Motion or instability is well known to prevent healing of a fractured bone, and to reduce bone-implant fixation by predictably producing a fibrous interfacial membrane around a joint replacement implant [16]. Another fundamental condition is the surgical preparation of the implant site, and whether line-to-line press-fit fixation is achieved, or whether there are localized gaps between the implant and bone [17,18]. These different features can be a main driver of differential results, yet may not be readily possible to include in numerical models [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%